Solution NMR of Nanoparticles in Serum: Protein Competition Influences Binding Thermodynamics and Kinetics - Xu, Joanna Xiuzhu; Fitzkee, Nicholas C. (Frontiers in Physiology, 2021)
The spontaneous formation of a protein corona on a nanoparticle surface influences the physiological success or failure of the synthetic nanoparticle as a drug carrier or imaging agent used in vivo. A quantitative understanding of protein-nanoparticle interactions is therefore critical for the development of nanoparticle-based therapeutics. In this perspective, we briefly discuss the challenges and limitations of current approaches used for studying protein-nanoparticle binding in a realistic biological medium. Subsequently, we demonstrate that solution NMR spectroscopy is a powerful tool to monitor protein competitive binding in a complex serum medium in situ. Importantly, when many serum proteins are competing for a gold nanoparticle (AuNP) surface, solution NMR is able to detect differences in binding thermodynamics and kinetics of a tagged protein. Combined with other experimental approaches, solution NMR is an invaluable tool to understand protein behavior in the nanoparticle corona.